EFFECT OF BASIC SKILLS IN ANY SITUATION TESTS ACCURACY YOUNG PLAYERS - Artan R. Kryeziu (Sport Mont, 2013)
The paper aims to establish the impact of basic motor skills in some situational accuracy tests in youth basketball game. In a sample of 60 tested age of 17 year + / - 6 months. We have applied eigjt variables to the tested persons, five of which are predicting, while the other three are criterion tests. Connectivity between motor variables is handled through the correlation of Pearson. The impact of variables predicting in those criteria used in regression analysis. Also significant importance is given to the introduction of connectivity between basic motor skills in several accuracy tests typical for the basketball game situations. Regarding the basic motor skills variables have attained significant coherence, however situational space test throwing the ball in the basket in the same direction and shooting the ball in the basket in the corner 450 degres no coherence with any test has been shown from the space of the appility of basic motor skills. Through regression analysis procedure we’ve reviewed the impact of basic motor skills in some situational accuracy tests. Treat analysis of criterion variables in those predicting we can say that accuracy to situational variables impact junior league players had explosive force. Therefore we can conclude that explosive strength is a quite important factor in the game between young basketball players, with there moving actions the playes can achive their goal of scoring points.